Microvascular impairments detected by optical coherence tomography angiography in multiple sclerosis patients: A systematic review and meta-analysis - Liu, Jing; Song, Shuang; Gu, Xiaoya; Li, Hui; Yu, Xiaobing (Frontiers in Neuroscience, 2023)
Purpose A systematic review and meta-analysis was conducted to investigate changes in retinal and choroidal microvasculature in patients with multiple sclerosis (MS) using optical coherence tomography angiography (OCTA). Methods PubMed and Google Scholar were searched for studies that compared retinal and choroidal microvasculature between MS and healthy controls (HC) with OCTA. MS patients were divided into 2 groups: MS with (MSON) or without optic neuritis (MSNON). Results Totally, 13 studies including 996 MS eyes and 847 HC eyes were included. Compared with the HC, the vessel density of the whole superficial vascular complex (SVC) was reduced by 2.27% and 4.30% in the MSNON and MSON groups, respectively. The peripapillary vessel density was 2.28% lower and 4.96% lower in the MSNON and MSON groups, respectively, than in the HC. Furthermore, the MSON group had significant lower vessel density of the SVC (mean difference [MD] = −2.17%, P < 0.01) and lower peripapillary vessel density (MD = −2.02%, P = 0.02) than the MSNON group. No significant difference was found in the deep vascular complex or choriocapillaris densities among MSNON, MSON or HC groups (P > 0.05). Meta-regression analyses suggested that illness duration and the Expanded Disability Status Scale scores of MS patients were possible sources of heterogeneity (P < 0.05). Conclusion The retinal SVC and peripapillary vessel density decreased significantly in MS eyes, especially in eyes with optic neuritis. Retinal microvasculature is a potential biomarker of disease progression in MS.